OPTIMALISASI KUOTA TIGA PULUH PERSEN KETERWAKILAN PEREMPUAN DALAM DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) PROVINSI SUMATERA BARAT PADA PEMILU LEGISLATIF TAHUN 2014 - Agus Susanto; Andi Mustari Pide (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
Law Number 8 Year 2012 has stipulated the representation of women in general elections as affirmative provisions, and as a follow up the General Election Commission (KPU) stipulates the requirement of women representation of at least thirty percent as candidates for legislative member for political parties participating in the election. But empirically the results of legislative elections in 2014 have not been on the side of women, because it turns out the seats of members of the Regional House of Representatives (DPRD) West Sumatra Province is dominated by men and less than ten percent filled female members. If examined from the rules of fulfilling the quota of thirty percent female representation, then the omposition of members of West Sumatra Provincial DPRD is not in accordance with the provisions of the law. This condition shows not yet representation and not optimally empower women in politics in West Sumatra.